RESULTS OF APPLICATION OF SOFTENING SPHERICAL DISC WORKING ORGANNI IN FRONT OF THE BASE SMOOTHING BUCKET (ResearchJet Journal of Analysis and Inventions, 2021)
In this paper, based on the experimental results of the application of softening discs’ device in front of the straightener shovel, the results of the study of changes in the shape, hardness, volume weight, aggregate composition, level of leveling and tensile resistance in front of the shovel are described, depending on the speed of the aggregate.